Pengaruh Kualitas Pelayanan dan Persepsi Harga terhadap Tingkat Kepuasan Pelanggan Pengguna Jasa Pelayanan Driver Grab - Lala Nurmala; Abu Sayid Yusuf; Eman Sulaeman (Journal on Education, 2023)
In the city of Karawang, the use of online ojek transportation is one of the most effective transportation options, although it is felt to be a little more expensive, because it is able to provide better service, considering that it is not bound by routes and service hours. Grab is a mobile application-based motorcycle taxi service through its services. Therefore, quite a lot of Grab application users order motorcycle taxis using the mobile application online, after which the passengers will be picked up by motorcycle taxi drivers who will respond to orders from Grab users or from potential passengers. This study aims to determine the effect of service quality and price perceptions on customer satisfaction using Grab driver services in Karawang. This type of research is explanatory research with sampling using nonprobability sampling approach and purposive sampling technique. The data collection technique used a questionnaire in the form of a Google form aimed at users of the Grab online transportation service in Karawang City. Respondents in this study amounted to 100 people. The data analysis technique used was regression analysis using SPSS version 22 software. The results concluded that service quality had a positive and significant effect on customer satisfaction, price had a positive and significant effect on customer satisfaction, and service quality and price had a significant effect together. (simultaneously) on customer satisfaction using Grab online transportation services in Karawang City.